Table of Content - -, (Journal of Educational and Psychological Sciences, 2023)
Table of Content:1. Role of Virtual Classrooms in Achieving Learning Satisfaction During COVID-19 for Students of Taiba UniversityCo-Prof. Rofaydah Adnan Al-Ansary2. Obstacles of Applying E-Training in the Training and Professional Development Centers in the Sultanate of Oman from the Point of View of the TrainersMr. Sulaiman Khalaf Saeed Al-Makhashni , Dr. Jamilah Hamid3. The effect of cooperative learning on improving the performance level of some sport skills for 11th eleventh grade students in Muscat GovernorateMr. Dawod Amerv Al-Defaye , Co-Prof. Mahfoodha Sulaiman Al-Kitani , Co-Prof. Naser Yasser Al-Rawahi4. The level of Arabic language teachers' ability to develop skills Critical speaking among high school studentsProf. Mahmoud Helal Abdelkader5. The Reality of Educational Supervision in the Schools of Ramallah and Al- Bireh Governorate from the School Principals Point of ViewCo-Prof. Ashraf Mohammad Abu Khayran , Mrs. Nancy Rimon Rantisi6. The reality of inclusive government school principals exercising their supervisory role on the inclusive education program in the capital, Amman from their own point of viewDr. Yahya Ahmad Alqabali , Dr. Samy Sulyman Mahasees7. The level of knowledge of the skills of teaching reading comprehension based on effective instruction for teachers of learning disabilities in JeddahMrs. Wafa Yahia Mobajar , Co-Prof. Reem Mahmoud Gharib8. The level of Psychological Immunity among Secondary School Female Students in the Capital's secretariat-Sana'a.Mrs. Afrah Qasem Yehia Al-Ammari , Co-Prof. Elham Abdullah Mohammed Al-Eryani
Keywords: Journal of Educational and Psychological Sciences